BoGDB: An integrative genomic database for Brassica oleracea L. - Wang, Yong; Ji, Jialei; Fang, Zhiyuan; Yang, Limei; Zhuang, Mu; Zhang, Yangyong; Lv, Honghao (Frontiers in Plant Science, 2022)
Brassica oleracea is an important species due to its high economic and nutritional value. Moreover, it is an ideal model for studies of morphology and genome evolution. In the genomic era, with massive 'omics' data being generated, a high-efficiency platform is crucial to deepen our understanding of this important species. In this study, we developed the B. oleracea Genome Database (BoGDB) to consolidate genome, transcriptome, and metabolome data of B. oleracea cultivars, providing the first cross-omics platform for B. oleracea. In order to make full use of the multi-omics data, BoGDB integrates multiple functional modules, including 'Gene Search', 'Heatmap', 'Genome Browser', 'Genome', 'Tools', 'Metabolic', and 'Variation', which provides a user-friendly platform for genomic and genetic research and molecular design breeding of B. oleracea crops. In addition, BoGDB will continue to collect new genomic data of B. oleracea and integrate them into BoGDB when higher quality genomic data are released.